Evaluation of the risk of hypothyroidism and its clinical manifestations using the Zulewski scale - Ferreira-Hermosillo, Aldo; Toledo, Juan Omar; Cordoba, Karla (Frontiers in Endocrinology, 2024)
Background: Globally, clinical hypothyroidism affects an estimated 0.5 to 5% of the population, while subclinical hypothyroidism affects 5-20%. Limited data is available on the prevalence of thyroid disease within the Mexican population. The objective of this study was to describe the characteristics of people screened for hypothyroidism in Mexico during 2022 using the Zulewski scale.Methods: A cross-sectional analysis was conducted using data obtained from a digital survey administered by an e-Health platform. This study included participants of all genders, aged 18 years and older (n = 31,449). Descriptive statistics (frequencies and percentages) were sued to describe the data. Differences between groups were assessed through the chi-square or Fischer's exact test. Information gathered was subjected to hierarchical segmentation analysis to explore trends and patterns. Statistical significance was set as <0.05.Results: Among the participants, 87.7% were women, and 80% fell within the age group 18 and 44 years. According to the Zulewski scale, 27% of the participants had a low risk of hypothyroidism, 37.4% were classified as having an intermediate risk, and 35.6% were at a high risk. In people at high risk of hypothyroidism, the most common symptom was constipation (29.2%) whereas the most common sign was decreased speed of movement (26.2%). Inquiry of slow movements, dry skin, and facial edema allowed the identification of 90.2% of participants at high risk of hypothyroidism. Conclusions: In Mexico, a significant portion of the population is at an intermediate or high risk of hypothyroidism, requiring confirmatory diagnostic tests.